2019
DOI: 10.1590/1980-5373-mr-2019-0145
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Squeeze Casting on Microhardness and Microstructure of Al-3Cu-xSi Alloy

Abstract: Aluminum alloys of the ANSI series 319 present Si and Cu as the main alloying elements and the mechanical strength of these alloys can be improved by the precipitation of the metastable Al 2 Cu phase. Squeeze Casting is a casting process in which the cast metal is deposited in a metal mold and solidified under certain pressure exerted by a punch. This process provides changes in the microstructure which lead to changes in the mechanical properties of the material such as the increase in the microhardness of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Extreme high temperature results in coarse grain structure and excessive pressure causes particle damage, leading to reduced hardness [111] . Studies revealed that the addition of Sn to Mg/HA composites and the increase of Si concentration in Al-Si-Cu alloy resulted in an increased hardness [59,112] . A key consideration for improved hardness is the homogeneous distribution of the alloying and reinforcing phases in the matrix.…”
Section: Hardnessmentioning
confidence: 99%
“…Extreme high temperature results in coarse grain structure and excessive pressure causes particle damage, leading to reduced hardness [111] . Studies revealed that the addition of Sn to Mg/HA composites and the increase of Si concentration in Al-Si-Cu alloy resulted in an increased hardness [59,112] . A key consideration for improved hardness is the homogeneous distribution of the alloying and reinforcing phases in the matrix.…”
Section: Hardnessmentioning
confidence: 99%